Fish processing discards: A plausible resource for valorization to renewable fuels production, optimization, byproducts and challenges. (1st March 2023) - Saravanan, A.; Yuvaraj, D.; Senthil Kumar, P.; Karishma, S.; Rangasamy, Gayathri
Graphical abstract: Highlights: Fish waste free oil as a promising alternative feedstock for biofuel production. Production methods of biodiesel from fish residues were discussed in depth. The impacts of transesterification reaction parameters for optimal production of biodiesel are discussed. Future prospects and techno-economic analysis on fish waste oil has been addressed. Abstract: Considering the petroleum and fuel prices in India for the past ten years, it can be concluded that there is a huge need for alternative sources of energy. The fuels that are currently used are obtained from fossil fuels, which is on the verge of depletion because of its continuous exploitation. In addition, these fossil fuels emit toxic elements, polluting the atmosphere and causes health ailments, affecting both land and living beings. Production of eco-friendly sources of energy has increasingly gained importance because of the problems involving fossil fuels (nonrenewable sources), such as cost, global warming, and energy crises. Every year, almost millions of tons of lipid-rich fish wastes are dumped by the domestic markets. A part of these wastes is used in the production of animal feed and fertilizers, whereas a majority is discarded in the environment, causing pollution. Recently, research has found out that fish discards are promising alternatives for the production of biogas and biodiesel. This review focusses on the potential benefits of using fish waste in the manufacture of biofuels, as well as the advantages over other methods. In addition, other key factors that play a major role, such as the quality of fish waste that is being dumped, biofuel preparation method, and its utilization, will also be reviewed. Thus, this present study is useful for those who work in industries that process fish, manage fishery waste, and produce biofuel, making it beneficial for them to utilize these high organic wastes in an efficient manner, thereby introducing an alternate renewable biodiesel feedstock.